Study of Oxidative Cyclization Using PhI(OAc)2 in the Formation of Benzo[4,5]thiazolo[2,3-c][1,2,4]triazoles and Related Heterocycles – Scope and Limitations - Demmer, Charles S.; Jørgensen, Morten; Kehler, Jan; Bunch, Lennart (Synlett, 2014)
A one-pot, two-step reaction for the synthesis of benzo[4,5]thiazolo[2,3-c][1,2,4]triazoles and related heterocycles under mild conditions was herein developed. The key step of this transformation is an oxidative cyclization employing PhI(OAc)2 as reagent. Scope and limitations (group functionality tolerance and sterics) were studied showing the robustness of the present methodology which can be used as potential access to new fused heterocycle libraries.
Keywords: cyclization; heterocycles; fused-ring systems; substituent effects; condensation